Rights to land and extractive resources in Tanzania (2/2): The return of the state - Thabit Jacob; Rasmus Hundsbæk Pedersen; Faustin Maganga; Opportuna Kweka (Danish Institute for International Studies (DIIS), 2016)
Under recent policy reforms in Tanzania's extractive sectors, the state is taking centre stage in the governance and regulation of minerals and oil/gas/petroleum resources. Through state-owned companies it is also re-emerging as a more direct investor in these sectors. This affects the rights of other stakeholders, not least the multinational companies. This paper analyses the key features of contemporary mining and petroleum legislation and their implications for smallholders, investors and state actors. It argues that recent return of the state signifies a major shift in bargaining power between the state and other actors, especially multinational companies. At the same time, while smallholders saw a gradual strengthening of their rights, rights to land in extractive investments are still precarious. For local communities, although local content and CSR provisions have been strengthened, local content is often reinterpreted to mean national content. This may potentially disfavour communities that bear burdens of extraction at the sub-national levels.
Keywords: 330; Land; Mining; Petroleum; Gas; Rights; Investments; Tanzania